The Criticism Concept of Arabic Poetry in Ibn Qutaibah and Ibn Sallam Al-Jumahi Perspectives - NDR. Ayu Nurdiana; Tatik Mariyatut Tasnimah; Ghazali bin Zainuddin; Moh. Wakhid Hidayat (ALSUNIYAT: Jurnal Penelitian Bahasa, Sastra, dan Budaya Arab, 2023)
This study aims to compare with the analysis of the thoughts of Ibn Qutaiba and Ibn Sallam Al-Jumahi in Literary Criticism. The research methodology involves a qualitative analysis of the writings of Ibn Qutaibah and Ibn Sallam Al-Jumahi. The historical and cultural context in which these two scholars were writing is also considered in order to better understand their views on poetry criticism and how they reflect broader trends in Arabic literature. The data obtained are from books by the two critics, Al-Shi'r wa Al-Shu'ara and Tabaqat Fuhul As-Shu'ara. By comparing the two thoughts, the results of this study reveal that both Ibn Qutaibah and Ibn Sallam Al-Jumahi had similar criteria for evaluating poetry but differed in their emphasis on certain aspects of poetic form and content. Ibn Qutaibah concludes his assessment of the identity of poetry because his criticisms by looking at the suitability of its 'Arudh and Qafiyah. Meanwhile, Al-Jumahi criticizes the legitimacy of poems by revealing the identity of the poem its poet to see the originality or from which tribe (region) the poem originates.